Association between childhood BMI trajectories and cardiometabolic risk and mental health problems at the age of 13 years: the cohort STudy of Adolescence Resilience and Stress (STARS). (March 2023) - Chen, Yun; Dangardt, Frida; Friberg, Peter
Abstract: Background: Research on BMI trajectories has been focused mainly on childhood and adolescence, missing birth and infancy, which are also relevant in the development of cardiometabolic disease in adulthood. We aimed to identify trajectories of BMI from birth throughout childhood, and to examine whether BMI trajectories predict health outcomes at the age of 13 years; and, if so, whether differences exist among trajectories regarding timeframes during which BMI in early life influences health outcomes. Methods: Participants recruited from schools in the Västra Götaland region of Sweden completed questionnaires of perceived stress and psychosomatic symptoms and were examined for the following cardiometabolic risk factors: BMI, waist circumference, systolic blood pressure, pulse-wave velocity, and white blood cell counts. We collected ten retrospective measures of weight and height, from birth to the age of 12 years. Participants with at least five measures (at birth, one at age 6–18 months, two at age 2–8 years, and one at age 10–13 years) were included in the analyses. We used group-based trajectory modelling to identify BMI trajectories, ANOVA to compare different trajectories, and linear regression to assess associations. Findings: We recruited 1902 participants (829 [44%] boys and 1073 [56%] girls, median age 13·6 years (IQR 13·3–13·8). We identified and named three BMI trajectories, and categorised participants accordingly: normal gain (847 [44%] participants), moderate gain (815 [43%] participants), and excessive gain (240 [13%] participants). Differences distinguishing these trajectories were established before the age of 2 years. After adjustments for sex, age, migrant background, and parental income, respondents with excessive gain had a higher waist circumference (mean difference 19·2 cm [95% CI 18·4–20·0]), higher systolic blood pressure (mean difference 3·6 mm Hg [95% CI 2·4–4·4]), more white blood cells (mean difference 0·7 × 10⁹ cells per L [95% CI 0·4–0·9]), and higher stress scores (mean difference 1·1 [95% CI 0·2–1·9]), but similar pulse-wave velocity compared with adolescents with normal gain. Higher waist circumference (mean difference 6·4 cm [95% CI 5·8–6·9]), higher systolic blood pressure (mean difference 1·8 mm Hg [95% CI 1·0–2·5]), and a higher stress score (mean difference 0·7 [95% CI 0·1–1·2]) were also found in adolescents with moderate gain, compared with adolescents with normal gain. Regarding timeframes, we observed that a significant positive correlation of early life BMI with systolic blood pressure started approximately at the age 6 years for participants with excessive gain, much earlier than for participants with normal gain and moderate gain, for which it started at the age of 12 years. For waist circumference, white blood cell counts, stress, and psychosomatic symptoms, the timeframes were similar across the three BMI trajectories. Interpretation: Excessive gain BMI trajectory from birth can predict both cardiometabolic risk and stress and psychosomatic symptoms in adolescents before the age of 13 years. Funding: Swedish Research Council (grant reference 2014-10086).